The Definition and Delineation of the Target Area of Radiotherapy Based on the Recurrence Pattern of Glioblastoma After Temozolomide Chemoradiotherapy - Zheng, Lin; Zhou, Zhi-Rui; Yu, QianQian; Shi, Minghan; Yang, Yang; Zhou, Xiaofeng; Li, Chao; Wei, Qichun (Frontiers in Oncology, 2021)
Radiotherapy is an important treatment method for glioblastoma (GBM), but there is no consensus on the target delineation for GBM radiotherapy. Radiation Therapy Oncology Group (RTOG) and European Organization for Research and Treatment of Cancer (EORTC) have their own rules. Our center adopted a target volume delineation plan based on our previous studies. This study focuses on the recurrence pattern that does not include the peritumoral edema in the target delineation of patients with GBM. We prospectively collected 162 cases of GBM, and retrospectively analyzed the clinical data and continuous dynamic magnetic resonance images (MRI) images of 55 patients with recurrent GBM. All patients received concurrent radiotherapy and chemotherapy with temozolomide (TMZ). We defined that the Gross Tumor Volume (GTV) includes postoperative T1-weighted MRI enhancement area and postoperative residual cavity. Clinical Tumor Volume 1 (CTV1) and CTV2 were defined as GTV with 1 cm and 2 cm expansion. Planed Tumor Volume 1 (PTV1) and PTV2 were defined as the CTV1 and CTV2 plus a 3 mm margin respectively, with a prescribed doses of 60 Gy and 54 Gy respectively. The first recurrent contrast-enhanced T1-weighted MRI was introduced into the Varian Eclipse radiotherapy planning system and fused with the original localized Computed Tomography (CT) images to determine the recurrence pattern. The median follow-up time was 15.8 months. The median overall survival (OS) and progression-free survival (PFS) were 17.7 months and 7.0 months, respectively. Among them, 44 patients recurred in the irradiation center, 2 patients recurred in the radiation field, 1 patient had a marginal recurrence, 11 patients had distant recurrences, and 3 patients had subependymal recurrences. Five patients had multiple recurrence patterns at the same time. Compared with the EORTC's scheme, the target delineation that excludes the peritumoral edema makes a smaller brain volume exposed to high dose radiation (P = 0.000), and no increased risk of marginal recurrence and lower than 5% marginal recurrence rate. Based on the above, it is appropriate for GBM to delineate the target area excluding peritumoral edema.